Peningkatan Kemampuan Berbicara Bahasa Arab Siswa Madrasah Ibtidaiyah Melalui Thariqah Mubasyarah - Helmi, Yeniga; Hanif, Akhyar (JOEAI (Journal of Education and Instruction), 2023)
ABSTRACT The purpose of this study was to determine the improvement of students' Arabic speaking/muhadatsah skills through the use of the Thariqah Mubasyarah method in learning. This research is a Classroom Action Research (CAR) by taking a sample of class IV A students at the Gulai Bancah State Madrasah Ibtidaiyah (MIN) Bukittinggi City. The data was obtained through two cycles of class action activities. This study found that student learning outcomes through the tariqah mubasyarah method showed a very significant increase, namely; 1) the use of pronunciation increased from 11% to 73%, 2) the use of intonation from 11% to 60% and 3) the use of expression from 15% to 77%. This means that the value of students using the Tariqah Mubasyarah method has increased by an average of 70%. After the implementation of cycle I and cycle II, and the acquisition of pronunciation, intonation and expression values, there is no longer a value of 1. In general, students in muhadatsah are able to use pronunciation, intonation and expression well. This study concluded that learning Arabic using the tariqah mubasyarah method can improve students' Arabic speaking skills (muhadatsah) and have a positive effect on their learning outcomes. Keywords : Arabic; learning; muhadatsah;thariqah mubasyarah